2010
DOI: 10.1080/00224491003599744
|View full text |Cite
|
Sign up to set email alerts
|

Dance and Sexuality: Many Moves

Abstract: This literature review of dance and sexual expression considers dance and religion, dance and sexuality as a source of power, manifestations of sexuality in Western theater art and social dance, plus ritual and non-Western social dance. Expressions of gender, sexual orientation, asexuality, ambiguity, and adult entertainment exotic dance are presented. Prominent concerns in the literature are the awareness, closeting, and denial of sexuality in dance; conflation of sexual expression and promiscuity of gender a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 128 publications
1
51
0
12
Order By: Relevance
“…My findings are consistent with pockets of research on female strippers that suggests the objectification they experience while dancing leads to an improved self-concept (Barton 2007;Barton and Hardesty 2010;Halpern 1981;Hanna 2010;Ryan and Martin 2001). For instance, Barton and Hardesty (2010) found that some women experience what they refer to as "body ekstasis," which is the situation where dancers enjoy being objectified and desired by audience members.…”
Section: Discussionsupporting
confidence: 87%
“…My findings are consistent with pockets of research on female strippers that suggests the objectification they experience while dancing leads to an improved self-concept (Barton 2007;Barton and Hardesty 2010;Halpern 1981;Hanna 2010;Ryan and Martin 2001). For instance, Barton and Hardesty (2010) found that some women experience what they refer to as "body ekstasis," which is the situation where dancers enjoy being objectified and desired by audience members.…”
Section: Discussionsupporting
confidence: 87%
“…Women derive quality cues (e.g., physical strength) from men's dance movements and rate these cues as attractive (see for review Hanna 2010;Hugill et al 2010;Fink et al 2014). Comparably, little is known about the relationship of men's personality and women's assessments of dance attractiveness, although some research suggests that aspects of personality are conveyed through dance movements (Fink et al 2012;Hugill et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Dance is a complex form of human movement, which is observed in courtship situations in almost all human societies (see for review Hanna 1987Hanna , 2010Hugill et al 2010). It has been reported that male dance conveys aspects of mate quality such as physical strength (Hugill et al 2009;McCarty et al 2013) and sensation seeking (Hugill et al 2011), with dances of physically strong and risk-taking men rated more attractive by women.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hanna (2010), dance is a genre of expression and performance that is marked by struggles between the proper performance of masculinity and femininity. Although some forms of dance can create spaces of expression that challenge gender assumptions, such as the Ukrainian boy band Kazaky, whose members engaging in 'gender-bending' performances in high heels, competitive ballroom dancing is typically more rigidly policed.…”
Section: Ballroom Dancingmentioning
confidence: 99%